Effects of standardized ileal digestible tryptophan:lysine ratio in diets containing 30% dried distiller grains with solubles on the growth performance and carcass characteristics of finishing pigs in a commercial environment - Barnes, J.A.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two experiments were performed to determine the effects of increasing standardized ileal digestible (SID) tryptophan to lysine (trp:lys) ratio in growing-finishing pig diets containing 30% dried distillers grains with solubles (DDGS). In both experiments, soybean meal replaced crystalline lysine and threonine to alter the dietary SID trp:lys concentrations while maintaining minimum ratios of other amino acids. In Exp. 1, a total of 638 pigs (PIC 1050 × 337, initially 80.0 lb) were used in a 105-d trial with 26 to 27 pigs per pen and 6 pens per treatment. Pens of pigs were randomly allotted to 1 of 4 dietary treatments with standardized ileal digestible trp:lys ratios of 14.0, 15.0, 16.5, and 18.0%. All diets were fed in meal form and treatments were fed in 4 phases. For the overall trial, ADG and ADFI increased (linear; P < 0.001) as trp:lys increased through 18%; however, the response tended to be quadratic from d 0 to 42, with optimal ADG and ADFI at 16.5% SID trp:lys. Feed efficiency was not influenced by SID trp:lys ratio. Although feed cost per pig increased (linear; P < 0.001) as SID trp:lys ratio increased, so did (linear; P < 0.04) final live weight, HCW, income per pig, and income over feed cost (IOFC). The results of this experiment indicated the optimal SID trp:lys ratio was 16.5% from 80 to 160 lb, but at least 18% from 160 to 265 lb. In Exp. 2, a total of 1,214 pigs (PIC 1050 × 337, initially 146.2 lb) were used in a 73-d finishing trial with 25 to 28 pigs per pen and 9 pens per treatment. Pens of pigs were randomly allotted to 1 of 5 treatment groups. Pigs were fed common diets before the start of the experiment. Dietary treatments included corn-soybean meal-based diets with SID trp:lys ratios of 15.0, 16.5, 18.0, and 19.5, and the 15.0% diet with L-tryptophan added to achieve 18.0% SID trp:lys ratio. Overall (d 0 to 73), ADG, ADFI, F/G, final weight, and HCW improved (linear; P < 0.03) as dietary SID trp:lys increased through 19.5%. Increasing SID trp:lys increased (linear; P < 0.001) feed cost per pig, but also increased (P < 0.01) total income per pig. While there were no differences on an IOFC basis, pigs fed the highest level of SID trp:lys had numerically the greatest IOFC. Overall, there were no significant differences between the diet with 18.0% SID trp:lys and the diet with 15.0% SID trp:lys with added L-tryptophan to 18.0%. These experiments demonstrate there is opportunity to improve growth performance in late-finishing pigs with increased SID trp:lys ratios in diets containing high amounts of DDGS.
Keywords: Swine; Amino acid ratio; Dried distillers grains with solubles; Lysine; Tryptophan